The Impact of Intellectual Capital Configuration on Diversification in Banking Industry: Evidence from Indonesia - Aiyubi, Rangga Yusuf; Chalid, Dony Abdul (UI Scholars Hub, 2020)
Research Aims: This study aims to examine the impact of Intellectual Capital configuration on business diversification in Indonesian banking Industry Design/methodology/approach: This reseach employ panel data regression analysis, using data of 88 commercial banks in Indonesia druing the year of 2014 to 2019. Research Findings: The results of this study shows that Human Capital Efficiency and Structural Capital Efficiency affects the strategy of income diversification. While Capital Employed Efficiency affects the strategy of asset diversification. The results Theoretical Contribution/Originality: Previous research more focus on the effect of diversification on performance. Researche on how the internal capital of an organization affects the level of diversification in the banking industry is still limited. Using a country context where the banks are very heterogeneous (both in terms of size and intellectual capacity), this research can analyze how these differences affect the level of diversification. Managerial Implication in the South East Asian context: the aspects of human resources and internal processes greatly affect the diversification of banking products. Furthermore, diversification of bank assets will be strongly influenced by working capital, which is currently a concern for financial services authorities in some Asian countries. Research limitation & implications: The indicators used to measure intellectual capital in this study rely more on financial information in the financial statements. This indicator does not measure directly the intellectual capital of a bank organization.